Coming of age in a straight white man's geography: reflections on positionality and relationality as feminist anti-oppressive praxis. Issue 11 (1st November 2022) - Kinkaid, Eden; Parikh, Aparna; Ranjbar, A. Marie
Abstract: In this intervention, we consider how relational thinking about our positions and experiences can contribute to a feminist, anti-oppressive praxis in geography. Hosting a critical dialogue amongst ourselves, we collectively reflect on our experiences coming of age in a discipline marked by ongoing forms of coloniality, racism, sexism, and trans/homophobia in an attempt to find commonalities across our different identities and experiences. Drawing from feminist thought and situating these evolving and polyvocal concepts within our experiences as feminist geographers, we consider what relationality and its associated practices can accomplish within our institutions. We also critique how feminist approaches such as these are taken up and deployed in 'critical' spaces, yet often fail to transform power dynamics long characterizing the discipline and its institutional spaces. In doing so, we aim to develop a feminist geographic praxis that recognizes our fluid subjectivities and the different positions we inhabit in the academy while also contributing to a sense of solidarity and commonality-in-difference. We revisit and build upon feminist concepts of positionality and relationality to both name the identity politics of the field and to fashion a way toward more inclusive spaces shaped by mutuality, recognition, and an anti-oppressive praxis.